The durability of basalt-fiber-reinforced cement mortar under exposure to unilateral salt freezing cycles - Zhou, Jiguo; Wang, Guihua; Zhu, Guangxing (Frontiers in Materials, 2023)
Basalt fiber and cement-based materials have been widely applied in engineering structures. In this context, the durability of basalt-fiber-reinforced ordinary silicate mortar was systematically studied under exposure to unilateral salt freezing. The mechanical durability, chloride ion diffusion characteristics, and microscopic pore characteristics of cement mortar with basalt fiber content levels in the range of 0 kg/m3–1.5 kg/m3 were tested under exposure to 0–40 freeze–thaw cycles. The relationships of changes in the internal pore structure with mass loss, mechanical damage, and the physical properties of the material were also analyzed under exposure to salt freezing cycles. The results demonstrated that even a small amount of basalt fiber could significantly improve the mechanical properties of cement mortar under unilateral salt freezing and its resistance to salt freezing erosion. In particular, cement mortar with 1.2 kg/m3 basalt fiber content exhibited good durability of compressive and flexural strength, while the specimens with no basalt fibers exhibited a relatively large degree of internal porosity under exposure to unilateral salt freezing. Our work provides concrete evidence for changes in the porosity of mortar under exposure to unilateral salt freezing, with these changes showing an exponential relationship with mortar mass loss and a strong linear correlation with changes in the compressive strength, flexural strength, and chloride ion diffusion coefficient of the material.